Registration of IA100RPS and IA101RPS sorghum inbred lines for photoperiod‐sensitive biomass hybrids. Issue 2 (27th December 2021) - Salas‐Fernandez, Maria Guadalupe; Kemp, Joshua
Abstract: The sorghum [ Sorghum bicolor (L.) Moench] parental inbred lines IA100RPS (Reg. no. PL‐319, PI 698107) and IA101RPS (Reg. no. PL‐320, PI 698108) were developed by the Iowa State University sorghum breeding program in Boone, IA, and released in 2019. These restorer inbred lines were generated to provide the forage and biofuel industry with improved germplasm capable of producing photoperiod‐sensitive hybrids with high biomass yield adapted to northern latitudes. IA100RPS and IA101RPS were developed using the pedigree breeding method from the cross of P89008 and RTx2910. IA100RPS is a purple plant with red grain, ∼2.4 m tall, that flowers on average 70 d after planting. IA101RPS is a tan plant with red grain, ∼2.1 m tall, that flowers on average 72 d after planting. From 2015 to 2018, both lines were evaluated in testcross combinations with a set of public A‐lines in multiple locations in the state of Iowa. Hybrids generated with IA100RPS and IA101RPS had significantly higher biomass yield than those derived from RTx2910 and RTx2909, with superior lodging resistance and higher dry matter content. This germplasm adapted to northern latitudes represents novel inbred lines with good general combining ability for the production of photoperiod‐sensitive forage or biofuel hybrids and could be used as parental sources for the development of improved sorghum lines with adaptation to the midwestern United States. Core Ideas: Novel restorer lines were developed to produce photoperiod‐sensitive biomass hybrids. Pollinator parents are adapted to northern latitudes. Inbred lines in hybrid combination produce biomass yield superior to those of Tx2910 and Tx2909. IA100RPS‐ and IA101RPS‐derived hybrids are valuable for forage use and biofuel industry. IA100RPS and IA101RPS have good general combining ability with diverse public A‐lines.